Dynamic push–pull characteristics at three hand-reach envelopes: Applications for the workplace. (January 2016) - Calé-Benzoor, Maya; Dickstein, Ruth; Arnon, Michal; Ayalon, Moshe
Abstract: Pushing and pulling are common tasks in the workplace. Overexertion injuries related to manual pushing and pulling are often observed, and therefore the understanding of work capacity is important for efficient and safe workstation design. The purpose of the present study was to describe workloads obtained during different reach envelopes during a seated push–pull task. Forty-five women performed an isokinetic push–pull sequence at two velocities. Strength, work and agonist/antagonist muscle ratio were calculated for the full range of motion (ROM). We then divided the ROM into three reach envelopes – neutral, medium, and maximum reach. The work capacity for each direction was determined and the reach envelope work data were compared. Push capability was best at medium reach envelope and pulling was best at maximum reach envelope. Push/pull strength ratio was approximately 1. A recommendation was made to avoid strenuous push–pull tasks at neutral reach envelopes. Highlights: We investigated dynamic push pull strength and work measures during a seated task, at different reach envelopes. Dynamic pushing work capability was best at medium reach envelopes. Pulling was best at maximum, followed by medium, reach positions. A recommendation was made to avoid strenuous push–pull tasks at neutral reach envelopes. Push/pull strength ratio was approximately 1.00.